The Relationship between English Learning Experiences on Students' Motivation to Communicate in English - Abdullah Kafabih; Rozanah Katrina Herda; Wulan Nugraheni; Sharizan Sharizan; Dalwinder Kaur (Journal of General Education and Humanities, 2026)
This study examined the relationship between English learning experiences and students’ motivation to communicate in English among secondary school students in Yogyakarta, Indonesia. Employing a quantitative correlational design, the study involved 72 eleventh-grade students selected through convenience sampling. Data were collected using two self-report questionnaires that underwent expert validation. Pilot testing indicated marginal internal consistency for the English Learning Experiences scale (α = .612) and acceptable reliability for the Motivation to Communicate scale (α = .863). Descriptive results showed that students generally reported positive English learning experiences and high motivation to communicate. However, opportunities for authentic English use outside the classroom and students’ tendency to initiate communication remained comparatively limited. Simple linear regression analysis revealed a significant positive predictive relationship between English learning experiences and motivation to communicate, F(1,70) = 17.386, p < .001, accounting for 19.9% of the variance in motivation to communicate (R² = .199). The findings suggest that students with more positive learning experiences tend to report higher communicative motivation, although motivation is likely associated with additional psychological, social, and contextual factors. The study highlights the importance of supportive learning environments and meaningful communication opportunities. Future research should employ larger samples, longitudinal designs, and mixed-method approaches.